2014
DOI: 10.1177/1545968313517754
|View full text |Cite
|
Sign up to set email alerts
|

A Behavioral Manipulation Engages Right Frontal Cortex During Aphasia Therapy

Abstract: Background An aphasia treatment was designed to shift laterality from the left to right lateral frontal lobe during word production by initiating word-finding trials with complex left-hand movements. Previous findings indicated successful re-lateralization. Objective The current study was designed to ascertain whether the shift was attributable to the left-hand movement. Methods Using stratified random sampling, 14 subjects were equally divided between Intention (IT) and Control (CT) treatments. CT was ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 24 publications
0
38
1
Order By: Relevance
“…A number of behavioral studies in healthy individuals and patients with aphasia have shown that pre-activation of the motor system can improve language production (Hanlon et al, 1990; Hadar et al, 1998; Holle and Gunter, 2007; Dick et al, 2009; Meinzer et al, 2011a; Benjamin et al, 2014). Moreover, inhibition of M1 by cathodal-tDCS resulted in reduced language learning (Liuzzi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A number of behavioral studies in healthy individuals and patients with aphasia have shown that pre-activation of the motor system can improve language production (Hanlon et al, 1990; Hadar et al, 1998; Holle and Gunter, 2007; Dick et al, 2009; Meinzer et al, 2011a; Benjamin et al, 2014). Moreover, inhibition of M1 by cathodal-tDCS resulted in reduced language learning (Liuzzi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, intention treatment, which uses a left-hand movement to initiate word finding efforts, increases right relative to left frontal activity, demonstrating reorganisation of word retrieval for picture naming and category member generation. 57 Simple practice in word retrieval without the hand movement does not produce this re-organisation. In the relatively fluent patients in this study, the impact of this manipulation on right posterior perisylvian activity correlated with treatment gains.…”
Section: Non-language Behaviours For Therapeutic Neuromodulationmentioning
confidence: 98%
“…Rather, we administered anodal tDCS in both active conditions to the left primary motor cortex. Behaviorally, preactivation of the motor network by behavioral interventions or anodal tDCS resulted in improved language processing in healthy individuals and patients with poststroke language impairment (e.g., Meinzer et al, 2016;Benjamin et al, 2014;Meinzer, Lindenberg, Sieg, et al, 2014;Hadar, Wenkert-Olenik, Krauss, & Soroker, 1998). Moreover, inhibitory cathodal M1-tDCS has been shown to interfere with language processing (Liuzzi et al, 2008).…”
Section: Baseline Neural Network Organization and Impact On Tdcs Effectsmentioning
confidence: 99%